Late Pleistocene Climate and Dust Source From the Mobarakabad Loess–Paleosol Sequence, Northern Foothills of the Alborz Mountains, Northern Iran - Ghafarpour, Amin; Khormali, Farhad; Meng, Xianqiang; Tazikeh, Hossein; Stevens, Thomas (Frontiers in Earth Science, 2021)
Paleoclimatic investigation of loess-paleosol sequences from North Iran is important for understanding past changes in a region highly sensitive to shifts in precipitation, and along potential routes of past human migration. Here we present carbon and oxygen isotopic compositions of bulk carbonate (δ13Cbc and δ18Obc, respectively) coupled with particle size distributions (PSD) of samples from the Mobarakabad section, northern Iran, to study past wind dynamics and hydroclimate. We also present new initial clay sized Hf-Nd isotope results from key horizons in order to assess general dust sources. Variations of δ13Cbc and δ18Obc values of modern soils compared to paleosols allow reconstruction of late Pleistocene-Holocene climate change in the area. Our results show severe drought during a major eolian deposition phase (EDP) after 34 ka. The thickness and PSD of the C horizon of unit 5 (EDP after 34 ka) suggest significant shifts in loess sources and depositional environments at that time. Indeed, based on our new clay sized Hf-Nd data, we hypothesize that the loess unit 5 might originate from the young crustal source of the Alborz and Kopet-Dag mountains. In general, the PSD of C horizons in the section are bimodal in the silt fraction and the very small, very fine clay fraction, with a mode at c. 1 μm in the modern soil and paleosols, is possibly produced by weathering and pedogenic processes. There also appears to be a good correlation between δ13Cbc and δ18Obc values, differentiating phases of loess accumulation and paleosol formation and hence providing quantitative data for reconstructing paleoclimatic conditions in the study area.